Numerical Analysis of Forced Convection of Nanofluid under Turbulent Flow between Two Parallel Plates - Iman Pishkar; S. Mohammad Hoseini (Journal of Applied Mathematics)
As research shows, in new and renewable energy systems, including solar energy, the study of turbulent flow is of great importance due to its high efficiency in heat transfer. It is also used in petrochemical and oil industries and cooling systems. Therefore, this paper focuses on the turbulent heat transfer of nanofluid between two parallel plates and the effect of the volume fraction of nanoparticles on turbulent heat transfer is investigated. The nanofluid applied in the study was alumina-water. The beginning and the end of the walls were insulated, and the middle part was considered as the heat source. The two-equation κ-ɛ model was used to model viscosity of turbulent flow. The governing equations were solved simultaneously using the control volume method based on SIMPLER algorithm. In this study, the effects of the Reynolds’ number in the range of 104 to 5∗104, volume fraction of 0.01 to 0.04, and nanoparticle diameter of 20 nm to 100 nm on field flow and rate of heat transfer were examined. The influence of Brownian movement on heat performance was considered. Evaluation showed that increasing the Reynolds’ number decreased the thickness of the laminar sublayer in turbulent flow and increased temperature and velocity differences. These greater temperature and velocity differences resulted in increased heat transfer and decreased skin friction. The findings imply that heat performance improves when nanoparticles are added to basic fluid. With increasing volume fraction of nanoparticles, shear stress of the channel wall increases, and consequently, skin friction increases too. In addition, the effect of nanoparticle diameter on thermal and hydraulic performance was studied. It was found that heat transfer and skin fraction decreased in the presence of the larger nanoparticles.